KEKERASAN TERHADAP PEREMPUAN DAN PERCERAIAN DALAM PERSPEKTIF PEMBERDAYAAN PEREMPUAN - Galistya, Theresia Mutiara (Jurnal Dinamika Sosial Budaya, 2020)
The achievement of Indonesian s women empowerment through Gender Empowerment Measure (GEM) shows an increase in the last eight years. On the other hand, the increasing trend is also seen in the percentage of violence against women. Ideally, the increase in GDI is followed by a decrease in acts of violence. A study of the 2017 Indonesian Demographic and Health Survey s data and also on the Annual Note of The Women's National Commission in 2018 is conduct to illustrate the conditions of women's empowerment, violence against women, and divorce as a result of violence. This study used a qualitative approach with descriptive and comparative analysis. The results indicate that the two indicators of women's empowerment, that is women's participation in household decision making and women's control of her income were related to disagreement towards domestic violence. In general, the higher the participation and control that women have, the more women disagree with all reasons to justify beating husbands to wives. This shows that in the future this attitude can reduce domestic violence as a cause of divorce. However, this study needs a more comprehensive analysis. This study also recommends the need for strengthening gender-based legislation to eliminate violence against women and will have an impact on women welfare and family resilience.
Keywords: Gender; GEM; Domestic Violence; 2017 IDHS; Family Resiliences